Very young learners - Reilly, Vanessa; Ward, Sheila (Oxford Oxford university press, 2010)
Resource books for teachers give guidance on the key aspects of language teaching, and provide examples and discussion of actual classroom materials and techniques. This book contains advice and ideas for teaching children aged 3 to 6 years.
Contents.
Keywords: Language; Learning; Activities; Games; English - foreign language